1993
DOI: 10.1002/jgt.3190170204
|View full text |Cite
|
Sign up to set email alerts
|

Induced matchings in cubic graphs

Abstract: In this paper, we show that the edge set of a cubic graph can always be partitioned into 10 subsets, each of which induces a matching in the graph. This result is a special case of a general conjecture made by Erdos and NeSetiil: For each d 2 3, the edge set of a graph of maximum degree d can always be partitioned into [5d2/4] subsets each of which induces a matching. 0 1993 John Wiley & Sons, Inc. INTRODUCTIONThroughout this paper, we consider colorings of the edges of a graph with positive integers. Formally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 6 publications
2
79
0
Order By: Relevance
“…(Observe that the line graph of a planar graph with maximum degree 3 is a planar graph with maximum degree 4.) Independently, Andersen [1] and Horák, He, and Trotter [8] demonstrated that every subcubic graph has a strong edge 10-coloring, which implies that every subcubic graph with m edges has an induced matching of size at least m/10.…”
mentioning
confidence: 99%
“…(Observe that the line graph of a planar graph with maximum degree 3 is a planar graph with maximum degree 4.) Independently, Andersen [1] and Horák, He, and Trotter [8] demonstrated that every subcubic graph has a strong edge 10-coloring, which implies that every subcubic graph with m edges has an induced matching of size at least m/10.…”
mentioning
confidence: 99%
“…When dealing with cubic graphs, we have immediately that χ S (G) ≥ 5. We know that χ S (G) ≤ 10 (see [4] and [13]) for cubic graphs in general and χ S (G) ≤ 9 (see [15]) when considering cubic bipartite graphs (answering thus positively to conjectures appearing in [9] and [8]). …”
Section: Graphs With Strong Chromatic Indexmentioning
confidence: 73%
“…The conjecture was verified for graphs having ∆ ≤ 3 [1,12]. When ∆ > 3, the only case on which some progress was made is when ∆ = 4 and the best upper bound stated is χ ′ s (G) ≤ 22 [4].…”
Section: Introductionmentioning
confidence: 91%